Sonic Under Expanded Flow Control With Micro Jets - Syed, Syed Ashfaq; Khan, Sher Afghan (IJERA, 2013)
This paper presents the results of experimental studies to control the base pressure from a convergent nozzle under the influence of favorable pressures gradient at sonic Mach number. An active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed to control the base pressure. The area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied are 2.56, 3.24, 4.84 and 6.25. The L/D ratio of the sudden expansion duct varies from 10 to 1. From the results, an important aspect to be noted here is that, unlike passive controls the favorable pressure gradient does not ensure augmentation of the control effectiveness for active control in the form of micro jets. To study the effect of micro jets on the quality of flow in the enlarged duct wall pressure was measured and it is found that the micro jets do not disturb the flow field in the duct rather the quality of flow has improved due to the presence of micro jets in some cases.